2018
DOI: 10.1007/s13197-018-3482-6
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Swiss cheese ripening by microbial lipase without affecting its quality characteristics

Abstract: The effect of exogenous microbial lipase enzyme on the ripening of Swiss cheese (0, 200, and 800U lipase in 30 L milk) was investigated for the physicochemical, textural and sensory properties, along with its microstructure. The aim of this study was to investigate the application of microbial lipase to accelerate the ripening without affecting its original desirable quality characteristics. The effect of the microbial lipase was studied at different time periods (2, 30, 45, and 60 days) of the Swiss cheese ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…First, the lipase activity (PANGBO ENZYME, Nanning, China) is 100,000 U/g, and the recommended dose is 0.1 to 0.3%, i.e., 100 U/g to 300 U/g. Second, 100 to 300 U/g is a common addition in fermented products [8]. For example, Rani and Jagtap reported that 200 U/g of lipase was added to cheese, and the cheese maturation time was shortened from 90 days to 60 days while maintaining its quality [8].…”
Section: Preparation Of Suanzhayu Samplesmentioning
confidence: 99%
“…First, the lipase activity (PANGBO ENZYME, Nanning, China) is 100,000 U/g, and the recommended dose is 0.1 to 0.3%, i.e., 100 U/g to 300 U/g. Second, 100 to 300 U/g is a common addition in fermented products [8]. For example, Rani and Jagtap reported that 200 U/g of lipase was added to cheese, and the cheese maturation time was shortened from 90 days to 60 days while maintaining its quality [8].…”
Section: Preparation Of Suanzhayu Samplesmentioning
confidence: 99%
“…Starter enzymes throughout ripening link the ester bonds between glycerol and fatty acids in the triacylglycerides. Esterases analyse short acyl ester chains, whereas the longer acyl ester chains which are contained of more than 10 carbons were hydrolysed by lipases (Kendirci et al 2020 ; Rani et al 2019 ). In addition, the reduction in moisture value of Cheddar cheeses in the ripening period may be because of the biochemical variations and development of lactic acid which resulted in contraction of curd and which put an end to the aqueous stage of cheese.…”
Section: Discussionmentioning
confidence: 99%
“…Starter enzymes throughout ripening link the ester bonds between glycerol and fatty acids in the triacylglycerides. Esterases analyse short acyl ester chains, whereas the longer acyl ester chains which are contained of more than 10 carbons were hydrolysed by lipases (Kendirci et al 2020;Rani et al 2019). In addition, the reduction in moisture value of Cheddar cheeses in the ripening period may be because of the biochemical variations and development of lactic acid which resulted in contraction of curd and which put an end to the aqueous stage of cheese.…”
Section: Discussionmentioning
confidence: 99%